The most important persons in the management science: literature review - Viktoriya I. Borshch; V. V. Huz (Ринкова економіка: сучасна теорія і практика управління)
This article provides a deep research about the most known gurus of management: Henri Fayol, who invented the basic 14 Principles of Management, Michael Porter and his competition concept, at last Peter Drucker, the inventor of MBO system. Nowadays society is still using Fayol’s Porter’s and Drucker’s discoveries.